Neo-Khawārij Menace In Nigeria: Khalīfatu Calī’s Sliver Bullet As A Model To Address Bokoharam And Takfīrī Ideologies In The Country - Yusuph Dauda Gambari; Yahya Sahykh Ahmad (al-Afkar, Journal For Islamic Studies, 2023)
Boko Haram and Takfīrī are the two sects in Nigeria with the trait of Khawārij. Both have been making the headlines and forming the main topics of discussions on Islam in Nigeria in recent times. Their ideologies, activities, and approaches, especially the Boko Haram have called for more concerns because of their dreadfulness. These have also enabled their equation with the Khawārij sect in Islamic history, hence this paper aims to direct attention to the silver bullet of Khalīfatu cAlī in decimating them (Khawārij), especially now that the government's efforts in tackling BokoHaram have not been yielding the desired results. The historical method of research was adopted because the discussions are largely related to linking the past to the present. It is discovered that the government's efforts are failing because they focused on the aspects of military onslaught alone, whereas Boko Haram is both terrorism and religious extremism. It is through religion they recruit members for terrorism. Tackling them, therefore, called for dual approaches. Apart from military counter strategies, it also requires intellectual engagement as both were combined by Ali in his fights against Khawārij. The paper, therefore, concluded by recommending the creation of a Ministry for Religious Affairs (MRA) or Religious Affairs Commission (RAC) to coordinate and regulate religious matters, while the Nigeria Supreme Council for Islamic Affairs (NSCIA) is duly engaged by the government for intelligence gathering in stamping out Takfīrī and BokoHaram problems in the country